Current-mode CMOS Active Inductor with Applications to Low-Voltage Oscillators - Ma, M.; Li, Z.; Yao, Z. (Engineering, Technology & Applied Science Research, 2013)
This paper investigates a current mode active inductor. In the proposed active inductor, three current mirrors have been connected to each other to realize the negative feedback. This active conductor has a two layer transistor structure. A 4.257 GHz, 1.2-V power supply non-inductive LC negative resistor oscillator, base on two of the proposed active inductors, is demonstrated.